Enhancing Audiovisual Translation Classes through the Use of Aegisub Subtitling Software - Helmi Syukur; Muhammad Taufik; Nasrum (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
The integration of technology in subtitling practices has become increasingly significant, with various tools enhancing the quality and efficiency of audiovisual translation. Among these tools, Aegisub software stands out as a popular choice, particularly among fansub translators, due to its user-friendly interface and rich features. This study aims to explore the implementation of Aegisub in a subtitling course at the English Literature Department of UIN Alauddin, focusing on the experiences of fifth-semester students. Utilizing a qualitative approach, data were collected through classroom observations, interviews, and questionnaires, allowing for a comprehensive analysis of the students' challenges and successes while using the software. The findings reveal that while students effectively applied Aegisub to create subtitles, they encountered both technical and linguistic challenges. Technical issues included timing, typesetting, and codifying, while linguistic difficulties involved diction choices, equivalence, and translation strategies. Despite these challenges, the software's compatibility with various operating systems and its easy-to-follow instructions contributed to increased student motivation and engagement in subtitling tasks. This study highlights the dual nature of Aegisub as a valuable educational tool that not only facilitates learning but also presents challenges that need to be addressed for optimal use in audiovisual translation education